Employing surfactant-assisted hydrothermal synthesis to control CuGaO2 nanoparticle formation and improved carrier selectivity of perovskite solar cells - Papadas, Ioannis T.; Savva, Achilleas; Ioakeimidis, Apostolos; Eleftheriou, Polyvios; Armatas, Gerasimos S.; Choulis, Stelios A. (My University, 2018)
Delafossites like CuGaO2 have appeared as promising p-type semiconductor materials for opto-electronic applications mainly due to their high optical transparency and electrical conductivity. However, existing synthetic efforts usually result in particles with large diameter limiting their performance relevant to functional electronic applications. In this article, we report a novel surfactant-assisted hydrothermal synthesis method, which allows the development of ultrafine (∼5 nm) monodispersed p-type CuGaO2 nanoparticles (NPs). We show that DMSO can be used as a ligand and dispersing solvent for stabilizing the CuGaO2 NPs. The resulting dispersion is used for the fabrication of dense, compact functional CuGaO2 electronic layer with properties relevant to advanced optoelectronic applications. As a proof of concept, the surfactant-assisted hydrothermal synthesized CuGaO2 is incorporated as a hole transporting layer (HTL) in the inverted p-i-n perovskite solar cell device architecture providing improved hole carrier selectivity and power conversion efficiency compared to conventional PEDOT:PSS HTL based perovskite solar cells.
Keywords: Delafossite oxides; CuGaO2; Hole transporting layers; Perovskites solar cells; Printed electronics; Surfactant-assisted hydrothermal synthesis